2001
DOI: 10.1161/hc4601.099405
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Gene Transfer of a Secreted Transforming Growth Factor-β Type II Receptor Inhibits Luminal Loss and Constrictive Remodeling After Coronary Angioplasty and Enhances Adventitial Collagen Deposition

Abstract: Background-Extracellular matrix (ECM) remodeling is central to the development of restenosis after coronary angioplasty (PTCA). As a regulator of ECM deposition by vascular cells, substantial evidence implicates transforming growth factor-␤1 (TGF-␤1) in the pathogenesis of restenosis. We investigated the effects of intracoronary expression of a transgenic antagonist of TGF-␤1 on luminal loss after PTCA. Methods and Results-Porcine coronary arteries were randomized to receive a recombinant adenovirus expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 48 publications
6
76
0
2
Order By: Relevance
“…Several studies using gene transfer techniques have shown that locally enhanced TGF-␤ signaling enables matrix-rich neointima to develop in uninjured normal arteries of rats (11, 12). In contrast, localized blockade of TGF-␤ signaling results in the inhibition of neointimal formation, accompanied by reduced extracellular matrix synthesis in a rat balloon-injury model (13,14). Of clinical relevance is the observation that the expression levels of TGF-␤ mRNA in restenotic lesions are higher than those in primary atherosclerotic lesions (15).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using gene transfer techniques have shown that locally enhanced TGF-␤ signaling enables matrix-rich neointima to develop in uninjured normal arteries of rats (11, 12). In contrast, localized blockade of TGF-␤ signaling results in the inhibition of neointimal formation, accompanied by reduced extracellular matrix synthesis in a rat balloon-injury model (13,14). Of clinical relevance is the observation that the expression levels of TGF-␤ mRNA in restenotic lesions are higher than those in primary atherosclerotic lesions (15).…”
Section: Discussionmentioning
confidence: 99%
“…95 Adenoviral soluble TβRII can also inhibit constrictive remodeling after coronary angioplasty in pigs. 96 Pulmonary fibrosis has been successfully treated using adenovirus expression of decorin in the airway. 86 Administration of TGF-β antibodies prevents skin and lung fibrosis in murine sclerodermatous graft-vs-host 16 CM&R 2003 : 1 (January) Flanders and Burmester disease.…”
Section: Antagonists Of Tgf-β For Disease Treatmentmentioning
confidence: 99%
“…80 In this regard administration of adenoviral vectors of TGF-β or TGF-β antagonists is being widely used in animal models. 13,77,81,95,96 The administration of active-vs.-latent TGF-β is also an important consideration. Active TGF-β has a much shorter half-life than the latent form, 108 and active TGF-β may result in more side effects, since it is not subject to the activation step which is tightly controlled in vivo.…”
Section: Therapeutic Applications: Problems and Perspectivesmentioning
confidence: 99%
“…Generation of Ad5-lacZ and RAd36 has been described previously. 9,20,21 Ad5-PP-lacZ, Ad5-PMEP-lacZ and Ad5-PREP-lacZ were generated by homologous recombination in 293 cells. 22 Stocks were purified by CsCl gradient centrifugation and titered by serial dilution end point in HEK 293 cells.…”
Section: Generation Of Recombinant Adenovirusesmentioning
confidence: 99%